Chronic myeloid leukemia in patient with the klinefelter syndrome - Andreieva, S.V.; Korets, K.V.; Kyselova, O.A.; Ruzhinska, O.E.; Serbin, I.M. (Experimental Oncology, 2016)
Aim: Genetic inborn along with acquired diseases arise due to the lesions in genome of multipotent hematopoietic stem cells. The aim was to study an influence of constitutional anomaly, Klinefelter syndrome, and additional structural rearrangements on the BCR-ABL tyrosine kinase inhibitor targeted therapy efficacy. Material and Methods: We describe a 32-year-old male patient with chronic myeloid leukemia (CML) who was detected to have sex chromosomal abnormality during evaluation for Philadelphia chromosome. Results: At diagnosis of CML, two clones were detected by standard cytogenetic investigation of bone marrow cells: 1) clone with translocation t(9;22)(q34;q11), with two sex X chromosomes and absence sex chromosome Y; 2) clone with t(9;22) and unbalanced t(Y;20)(q11;q13). Analysis of blast transformed lymphocytes from peripheral blood showed karyotype 47,XXY. Monitoring of targeted therapy with second generation inhibitor of BCR-ABL tyrosine kinase indicated a cytogenetic remission and absence of BCR-ABL1 fusion signals after 11 months. Conclusions: Absence of translocation t(9;22)(q34;q11) in blast transformed T-lymphocytes at diagnosis of CML evidences that this translocation may appear not only at the level of multipotent haemopoietic cell progenitors but also may have oligo lineage myeloid origin. Presence of additional structural chromosomal abnormality in the clone with t(9;22)(q34;q11) does not affect the efficacy of therapy with the use of second generation BCR-ABL tyrosine kinase inhibitor.